Fibromyalgia, women and work in health: a dialectical essay on pain and detachment - André, Rosana Henrique da Silva (2022)
Fibromyalgia can be defined as a chronic, non-inflammatory pain syndrome of unknown etiology, which manifests itself in the skeletal muscle system, and may present symptoms in other apparatus, causing negative impact on the quality of life and activities of daily living of its carriers. As it is a disease that causes restriction of movements, it is understood that the worker may be affected, being necessary to be away from their work activities, thus reducing their quality of life. Thus, the following guiding question arose: What are the difficulties faced by patients with fibromyalgia in their work activities? And, to answer the guiding question, the following objective was elaborated: To identify the difficulties faced in quality of life and work performance by health workers with fibromyalgia. This is a descriptive study, done through the dissemination of an electronic questionnaire, containing open and closed questions, which had as its scenario the social networks of the Group of Integrative and Complementary Practices in Health - UFF and the participants of that group were part of the study. The methodology used for data analysis was the triangulation of methods. It is concluded that workload, rigid dynamics of activity control and ergonomic factors contribute as risk factors for the onset and chronification of restrictions imposed by fibromyalgia. It is proposed that the class of health workers should have a special focus, both in research, occupational risk studies and the establishment of actions of promotion, prevention and health education of the worker, with a view to improving their quality of life.